The Necessity of Establishing the Profit as a Tax Object - Bobur Bekmurod ugli Poyonov; Mohirakhon Dilshodbek kizi Yuldasheva (Researchparks Publishing, 2023)
Issues of rational taxing of profit based on science are covered. Opinions of economists on profit tax. The figures obtained from the practice were analyzed and suggestions and conclusions were formulated.